TINGKAT PREFERENSI MASYARAKAT MENGELOLA SAGU DI KABUPATEN ASAHAN, SERTA FAKTOR-FAKTOR YANG MEMENGARUHINYA - Rospita Odorlina Pilianna Situmorang; Alfonsus H Harianja (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
Lack of attention to the non-staple food sectors and changes in consumption pattern have resulted in decreasing of farmers' preference in cultivating sago, which ultimately results in the conversion of sago land including in Asahan District. This study aims to measure the level of community preference in managing sago and to reveal the factors that influence the level of people’s preference. Data were collected from 98 respondents by using questionnaire method and analyzed by descriptive statistical analysis, frequency tab, and spearman rank correlation. Research was conducted from May to December 2015 in Silo Bonto Village, Sei Paham Village, and Sungai II Hulu Village. The results showed that level of people’s preference in managing sago was moderate with an average value of 27.92. Ecological benefit factor from sago cultivation dominated the reason of community's interest in managing sago (40.48%), followed by economic factor (33.97%,) and sago consumption (25.54%). Socio-economic characteristics of respondents such as age, number of family dependents, farmland area, sago stands, and length of sago business have a significant correlation to the level of preference. Older farmers, fewer family dependents, sufficient farmland, and longer experience in sago palm utilization seem to prefer to manage sago cultivation.